تطبيق مبدأ الملائمة المكانية لمحطات الوقود في البصرة - الحويدر، عبدالرحمن جري مردان; جاسم، زينب أحمد (المنتدي الوطني لأبحاث الفكر والثقافة, 2018)
يعد النقل منظومة متكاملة وعصب الحياة الاقتصادية والاجتماعية لحياة مدينة البصرة، كونه يربط أجزاء المدينة المتناثرة بعضها مع بعض هذا من جهة، ومن جهة ثانية تزداد أهميته مع زيادة المساحة المخصصة ضمن نسيج المدينة، وهو بدوره يعد خدمة فعالة لسكان المدينة وإقليمها، كما يسهم في ترتيب استعمالات الأرض ومنها الخدمية، لذلك تعمل طرق النقل وضوابط ومعايير موقعية أخرى في التوزيع المكاني لمحطات تعبئة الوقود في المدينة، وبناءً عليه فإن محطات تعبئة الوقود إحدى الخدمات التي تقدمها مدينة البصرة إلى سكانها، لكونها توفر الوقود لكافة أنواع المركبات. شهدت محطات الوقود تغيرات كثيرة لاسيما في ازدياد أعدادها وتطور خصائصها الوظيفية والمكانية وبالتالي شغلت معظم قطاعات المدينة كونها قطاع استثماري يحقق عوائد ربحية مضمونة، كما وأصبحت تمثل نشاط تجاري منافس لاستعمالات تجارية وخدمية أخرى، وهذا يفسر تقاربها وزيادة تزاحمها في العديد من شوارع مدينة البصرة.
Transportation is an integrated system and the backbone of the economic and social life of the city of Basra, being linked to the scattered city parts of each other on one hand, on the other hand, it is becoming increasingly important as the area of the city's fabric is increased, which in turn is an effective service for the inhabitants and the territory of the city and contributes Monotonous uses of the land, including SOA, transport methods, controls and other site standards operate in the spatial distribution of the city's fuel filling stations, accordingly, fuel bottling plants are one of the services provided by Basra to their inhabitants, as they provide fuel for all types of vehicles. Fuel stations have undergone many changes, especially in their increasing numbers and development of their functional and spatial characteristics, and thus most of the city's sectors have occupied an investment sector that achieves secure profitability, and is a rival business activity for other commercial and service uses, which explains its convergence and increased crowding In many streets of the city of Basra.
Keywords: نظم المعلومات الجغرافية; البصرة; محطات الوقود; الملائمة المكانية